Correlation of Peripapillary Retinal Nerve Fibre Layer Thickness and Visual Evoked Potential in Optic Neuritis in a Tertiary Eye Care Centre - Godar, Manita Sunam; Sharma, Ananda Kumar; Thapa, Madhu; Sitaula, Sanjeeta; Gamal, Nita Sunam; Manandhar, Laxmi Devi (Nepalese Journal of Ophthalmology, 2019)
Introduction: Optic neuritis (ON) is the involvement of the optic nerve as a result of inflammation, demyelination or infection. Objective: To study the correlation between peripapillary retinal nerve fibre layer thickness (pRNFL) and visual evoked potential (VEP) in ON cases. Materials and Method: A non-interventional, descriptive, cross sectional study enrolling 66 eyes of 49 patients with ON was done. pRNFL thickness was measured by Optical Coherence Tomography (OCT) and VEP was also done. OCT and VEP findings were compared with the control group. In addition correlation between pRNFL thickness and VEP was done. Results: The mean pRNFL in affected eyes were significantly higher than the control superiorly (p-value<0.001), inferiorly (p-value <0.001), temporally (p-value 0.005) and nasally (p-value <0.001). The mean P100 latency in the affected eyes were significantly prolonged than the control eyes both at 1º (p-value<0.001) and at 15’ (p-value=0.05). The mean N75-P100 amplitude in the affected eyes were significantly reduced than the control eyes both at 1º (p-value<0.001) and at 15’ (p-value<0.001). The mean pRNFL thickness in all four quadrants and VEP findings of the affected eyes showed no significant correlation. Conclusion: The increased thickness in non-myelinated pRNFL has no correlation with the increased latency or decreased amplitude in cases of ON. However, OCT is seen as a useful tool in detecting and quantifying even subtle pRNFL changes in cases of optic neuritis.